The Greening of Africa (2) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The Greening of Africa / Harrison, P. Earthscan Books Ltd 3 Endsleigh Street London WCIH ODD UK